Wordsworth and Emerson: Aurora Borealis and the Question of Influence - Hall, Dewey (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractThis article concerns the question of influence evident in the transatlantic relationship between William Wordsworth and Ralph Waldo Emerson. I argue that influence is linked vitally to light—celestial or the northern lights (i.e. aurora borealis)—, which is evident in the prose and poetry by Wordsworth and Emerson. Electromagnetic energy conducts a circuit; this is reflected also in the transatlantic crosscurrent of the precursor and progeny. Notably, Wordsworth’s “The Complaint of a Forsaken Indian Woman” (1798) and his Preface to Lyrical Ballads (1802) influence Emerson’s The Poet (1844), which has been informed also by Michael Faraday’s Experimental Researches in Electricity (1839). The matter pertaining to influence is inextricably connected to electromagnetism, light, and aurora borealis that appear in the work by Wordsworth and Emerson. Inspiration, then, ultimately can be derived from a celestial source in relation to the terrestrial.